IMPLEMENTATION OF FACIAL RECOGNITION TECHNOLOGY AS A SERVICE INNOVATION FOR TRAIN PASSENGERS AT TUGU STATION, YOGYAKARTA - Andarini, Siska Ayu; Mediana, Risna (Yayasan Education and Social Center, 2025)
Face Recognition (FR) is a facial recognition technology used for check-in upon train departure. This study aims to determine the implementation of facial recognition technology in the passenger service system and identify the technical and non-technical challenges encountered. This study employed qualitative methods, collecting data using observation, documentation, and interviews. The interview method used was followed by data analysis and development using observations conducted by the author at the Face Recognition Unit at Yogyakarta Main Station during the research period of March-August 2025. The results show that the implementation of Face Recognition (FR) involves registration and data verification in the Access By KAI application or by visiting the departure station directly. Customers can then board directly through face recognition access by scanning their faces with a camera. Implementation of supporting systems and infrastructure with high-resolution cameras for facial scanning and ISO27001-certified cyber protection systems. Technical constraints include lack of stability and performance in the real-time data verification process, lack of accuracy in the lighting system, and the system's lack of sensitivity in recognizing customer data. Non-technical constraints include lack of customer trust, lack of socialization and education, and limited use, especially for toddlers, the elderly, and foreign nationals.